BS EN IEC 62841-3-7 AMD AA. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 3-7. Particular requirements for transportable wall saws (20th August 2020) - British Standards Institution,
No abstract available